2015
DOI: 10.2460/javma.247.2.190
|View full text |Cite
|
Sign up to set email alerts
|

Clinical disease associated with epizootic hemorrhagic disease virus in cattle in Illinois

Abstract: This large-scale outbreak of EHDV in US cattle was unusual because calves were affected. Because there is no way to effectively predict or prevent an EHDV outbreak in cattle, development of a vaccine for use in cattle during an outbreak would be beneficial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…Lymphopenia has not been described as a feature of EHD in cattle; however, the experimental reproduction of the disease in cattle has been rather challenging [111]. Infection-related fatalities in cattle have generally been attributed to sequelae rather than acute EHD [50]. This highlights the critical need to better understand EHDV pathogenesis in cattle in order to evaluate and mitigate potential impacts of EHDV to the economically important cattle industry.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lymphopenia has not been described as a feature of EHD in cattle; however, the experimental reproduction of the disease in cattle has been rather challenging [111]. Infection-related fatalities in cattle have generally been attributed to sequelae rather than acute EHD [50]. This highlights the critical need to better understand EHDV pathogenesis in cattle in order to evaluate and mitigate potential impacts of EHDV to the economically important cattle industry.…”
Section: Discussionmentioning
confidence: 99%
“…In the U.S., a large multi-serotype outbreak across 15 states which caused clinical disease and deaths in cattle occurred in 2012 [14]. This was followed by a 2013 outbreak of smaller geographic scope, but with an unusually high cattle case fatality rate of 26% (16/61) of EHDV-infected animals [50]. A recent study comparing the viral genomes of EHDV-2 isolates taken from deer and cattle during the 2012 event in the U.S. did not identify significant genetic changes to support an increased virulence of these viruses, and suggested that environmental factors such as drought conditions likely contributed to the increased morbidity and mortality in cattle [51].…”
Section: Ehd's Evolving Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…During fall of 2013, the first EHD outbreak in domestic ruminants was reported in Illinois. At least 18 cattle herds in northwestern Illinois were affected 41 . This outbreak coincided with the EHD outbreak affecting wild WTD in that region 41 and followed the major outbreaks in domestic ruminants in the USA in 2012 28 .…”
Section: Introductionmentioning
confidence: 99%
“…Although EHDV- 1, 2 and 6 are endemic in various areas of North America, South America and the Caribbean Basin, no clinical outbreaks in cattle had been reported (Verdezoto et al, 2017; Viarouge et al, 2014; Anbalagan & Hause, 2014; Allison et al, 2010) until 2013, when EHD was reported in cattle from Illinois, USA following an outbreak in deer in the same location in 2012 (Stevens et al, 2015). Viral antibodies were confirmed to be present in the cattle, but the EHDV serotype was not identified (Garrett et al, 2015). Previous serological studies identified EHDV- 1 and 2 to be circulating in the Caribbean Basin and South America (Gumm et al, 1984) and more recent studies have shown the presence of EHDV-6 in the Caribbean islands of Guadeloupe and Martinique and in French Guiana on the South American mainland (Viarouge et al, 2014).…”
Section: Introductionmentioning
confidence: 99%